Distinct mechanisms mediate naïve and memory CD8 T-cell tolerance - Jellison, Evan R. (National Academy of Sciences, 2012)
Peripheral tolerance to developmentally regulated antigens is necessary to sustain tissue homeostasis. We have now devised an inducible and reversible system that allows interrogation of T-cell tolerance induction in endogenous naïve and memory CD8 T cells. Our data show that peripheral CD8 T-cell tolerance can be preserved through two distinct mechanisms, antigen addiction leading to anergy for naïve T cells and ignorance for memory T cells. Induction of antigen in dendritic cells resulted in substantial expansion and maintenance of endogenous antigen-specific CD8 T cells. The self-reactive cells initially exhibited effector activity but eventually became unresponsive. Upon antigen removal, the antigen-specific population waned, resulting in development of a self-specific memory subset that recalled to subsequent challenge. In striking contrast to naïve CD8 T cells, preexisting antigen-specific memory CD8 T cells failed to expand after antigen induction and essentially ignored the antigen despite widespread expression by dendritic cells. The inclusion of inflammatory signals partially overcame memory CD8 T-cell ignorance of self-antigen. Thus, peripheral CD8 T-cell tolerance for naïve CD8 T cells depended on the continuous presence of antigen, whereas memory CD8 T cells were prohibited from autoreactivity in the absence of inflammation.